2015
DOI: 10.2196/jmir.3344
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of an E-Learning Course on Breast Imaging for Radiographers: A Stratified Randomized Controlled Trial

Abstract: BackgroundMammography is considered the best imaging technique for breast cancer screening, and the radiographer plays an important role in its performance. Therefore, continuing education is critical to improving the performance of these professionals and thus providing better health care services.ObjectiveOur goal was to develop an e-learning course on breast imaging for radiographers, assessing its efficacy, effectiveness, and user satisfaction.MethodsA stratified randomized controlled trial was performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
0
26
0
3
Order By: Relevance
“…Quantitative analysis.a) Practitioners across three breast screening sites behave differently in the application of compression force. There was also internal variability inside screening sites in compression force and thickness.a) 8[34]PortugalTo develop an e-learning course on breast imaging for radiographers and evaluate the course.RCT target group radiographers ( n  = 120) and radiology students ( n  = 70).Measures: efficacy, effectiveness and user satisfaction. Quantitative analysis.E-learning group got better scores in knowledge and course satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis.a) Practitioners across three breast screening sites behave differently in the application of compression force. There was also internal variability inside screening sites in compression force and thickness.a) 8[34]PortugalTo develop an e-learning course on breast imaging for radiographers and evaluate the course.RCT target group radiographers ( n  = 120) and radiology students ( n  = 70).Measures: efficacy, effectiveness and user satisfaction. Quantitative analysis.E-learning group got better scores in knowledge and course satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Using E-learning, educators can achieve a great possibility of easily and quickly update content [10]. Several studies demonstrate that radiographers are very receptive to this learning method [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…E-learning platform has been used to overcome the limitation of the traditional educational methods. Moreira et al (2015) developed an e-learning course on breast imaging for radiographers. They concluded that it was effective and highlighted the need for continuing education.…”
Section: Discussionmentioning
confidence: 99%